What factors are influencing tea consumption among Chinese urban residents? An empirical study. (17th November 2015) - Chen, Fuqiao; Li, Shujie; Jiang, Renhua; Jiang, Aiqin
Abstract: Using primary data collected from a questionnaire survey in 12 cities in China, we set up a model to analyze the influencing factors of Chinese urban residents' tea consumption. Three groups of factors are considered in the model, i.e., demographic and personal characteristics, economic factors and consumption habits. Research findings indicate that tea consumption is significantly impacted by gender difference, personal income, consumption atmosphere and habitual factors. This has important policy implications for tea marketing. First of all, it is essential to develop more tea products that cater to the needs of urban females while at the meantime securing the steady growth of tea consumption among males. Second, in light of the consumption discrepancies between families, areas and occupations, differentiated marketing strategies should be created with an emphasis on cultivating and taking advantage of consumption atmosphere in the society. In addition, income disparities call for diversified tea products with affordable prices. It is also suggested that educational programs on tea consumption be advocated to promote the consumption frequency and quantity of tea both in China and in other countries.